2022
DOI: 10.1007/s00339-022-06099-3
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic nanocomposite anatase–rutile TiO2 coating

Abstract: Nanocomposite TiO2 coatings of mixed anatase-rutile crystalline polymorphs with strong adherence to glass substrates were prepared via spray-plasma deposition method. The rutile content was varied between 0 and 30 mol%. The coating showed an enhanced photocatalytic activity towards cefixime antibiotic decomposition in aqueous solutions under UVA (=365 nm) light illumination. The activity significantly increased after the rutile phase formation, suggesting a synergetic effect of the two-component solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…and initial concentration of amoxicillin of 17 mg L −1 under 240 min of solar irradiation due to a synergistic effect. In addition, several other studies have also been reported using TiO 2 , [157][158][159] and supported TiO 2 160 on the photocatalytic remediation of amoxicillin. 3.2.1.2 ZnO and other metal oxides.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 75%
See 3 more Smart Citations
“…and initial concentration of amoxicillin of 17 mg L −1 under 240 min of solar irradiation due to a synergistic effect. In addition, several other studies have also been reported using TiO 2 , [157][158][159] and supported TiO 2 160 on the photocatalytic remediation of amoxicillin. 3.2.1.2 ZnO and other metal oxides.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 75%
“…These studies showed 84.12% degradation of amoxicillin after 240 min under optimum conditions of pH 9.5, catalyst dose of 1.5 g L −1 and initial concentration of amoxicillin of 17 mg L −1 under 240 min of solar irradiation due to a synergistic effect. In addition, several other studies have also been reported using TiO 2 , 157–159 and supported TiO 2 160 on the photocatalytic remediation of amoxicillin.…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 97%
See 2 more Smart Citations
“…27 There are also diffraction peaks of rutile TiO 2 crystals (JCPDS: 21-1272) at 27.51, 36.11 and 54.41, corresponding to the crystal faces (110), ( 101) and (111), respectively. 28 Therefore, its structure has a mixed crystalline phase (anatase and rutile). The overall peak positions of LMO are essentially the same as that of the standard card (JCPDS: 01-072-6619), 29,30 The results show that the prepared lanthanum manganate powder has a hexagonal perovskite structure.…”
Section: Resultsmentioning
confidence: 99%